Effect of carburizing process on bending fatigue performance of notched parts of 18CrNiMo7-6 alloy steel. (May 2023) - Qin, Shengwei; Wang, Lianxiang; Di, Liyin; Zhang, Chenghao; Zhao, Minghao
Highlights: Carburizing improve the fatigue performance of notched specimens significantly. The macro-plasticity has little effect on the fatigue performance. Carburizing reduce the notch sensitivity of notched specimens. The fatigue sources of the notched specimens are on the root surface of the notch. During fatigue, carburized specimens retain a portion of stable retained austenite. Abstract: Since stress concentration is easily formed at the notch, improving the fatigue performance of notched parts is critical. The carburizing process is widely used to manufacture notched parts. In this research, the effects of carburizing process and notch stress concentration on fatigue performance were analyzed by bending fatigue tests. In addition, the microstructure and hardness evolution processes of the carburized notched 18CrNiMo7-6 specimens were observed quasi-in situ. The results showed that macro-plasticity has little effect on the bending fatigue performance of notched samples and that the improvement in fatigue performance is primarily attributable to the high hardness and residual compressive stress introduced by carburizing. The fatigue notch sensitivity is therefore reduced after carburizing. Compared to the uncarburized specimens, the fatigue limit of the carburized specimens is increased by up to 128%. With the increase of the effective hardening layer depth, the fatigue limit increases first and then decreases. Moreover, the brittle phase transformation product (twinning martensite) of metastable retained austenite is easy to produce stress concentration. Conversely, the 'film-like' retained austenite with an extremely high stability can effectively avoid the phase transformation products.